Post-Match Changes in Muscle Damage Markers among U-21 Soccer Players - Nebojsa Trajkovic; Goran Sporis; Tomislav Vlahovic; Dejan Madic; Marko Gusic (Montenegrin Sports Academy, 2018)
Th is study aimed to investigate the eff ect of offi cial soccer matches on selected markers of muscle damage in U-21 soccer players. A group of 19 trained, healthy male soccer players from the junior category took part in this study. Blood samples were assessed pre-match and immediately aft er a match in response to a competitive (2×45 min) soccer match. Analysis was performed for muscle damage and infl ammatory markers. Signifi cant diff erences between two measures (before and aft er soccer match) exist in Aspartate-aminotransferase (AST), Lactate dehydrogenase (LDH), and Myoglobin. Plasma K+ signifi cantly decreased aft er the match (p<0.05), whereas plasma Na+ decreased slightly. Th is study showed that most selected markers of muscle damage were infl uenced by a soccer match. However, results remain inconsistent because of the infl uence of the type, duration, and intensity of exercise. Moreover, some markers show great variability among individuals.